Antimicrobial activity of hydroxytyrosol: a current controversy. Issue 4 (2nd April 2016) - Medina-Martínez, María S; Truchado, Pilar; Castro-Ibáñez, Irene; Allende, Ana
Abstract: This study focus on the main factors that affect the antimicrobial capacity of hydroxytyrosol, including the concentration (200, 400, and 1000 μg/mL), target strains, and the culture media (nutrient-rich and less-rich culture media). The potential HT degradation was also evaluated by HPLC-PAD. Kinetic parameters from growth curves showed that HT concentrations produced a doses-dependent shift when compared to the untreated control. In most of the cases, the highest tested dose (1000 μg/mL) was needed to inhibit growth of the selected strains. However, all the strains were able to grow even at the highest HT dose when cultivated in nutrient-rich culture media. It was observed that HT concentrations were reduced by about 15%, except for Escherichia coli 533 and 679 in Muller Hinton broth, where HT was reduced up to 35%. The results showed a limited antimicrobial activity, contrary to information previously published in some research papers. Abstract : :